Total replacement of the bladder urothelium with autologous colon mucosa. Experimental anatomical and functional study. - Rodríguez-Gutiérrez, Luis; Preciado-Preciado, Filiberto; Portilla-de Buen, Eliseo; García-Martínez, David; Palafox-Rodríguez, Miguel H. (Boletín del Colegio Mexicano de Urología)
Background: Chronic inflammation and transitional cell carcinoma originate from the urothelium. While treatment may involve partial or total removal of the bladder, Hansen initially used total mucosal denudation to treat cancer, but abandoned this technique due to complications. In selected cases, bladder preservation is sought as a treatment option for cancer. Objective: To determine whether colon mucosa can be implanted in a bladder completely denuded of its native mucosa, while preserving its anatomy and function. Material and method: An experimental study was conducted on dogs to replace the bladder mucosa entirely with autologous colon mucosa. The following were analyzed before and after the procedure: clinical course, laboratory studies, radiological evaluations, cystometry, and histopathological examination of the bladder. Results: The clinical course was satisfactory. Laboratory studies, including complete blood count, urea and creatinine levels, serum electrolytes, and general urinalysis, remained within normal limits (p = 0.28-0.86). Urine culture revealed Escherichia coli in all animals postoperatively (p = 0.01). Cystography was normal. Excretory urography remained normal in 9 out of 10 kidney units. Cystometry showed normal pressure but postoperative decrease in bladder capacity, which was not statistically significant (p = 0.218). Histopathological examination revealed normal kidney structure. Macroscopically, the bladder showed successful graft implantation, while microscopic analysis confirmed the presence of normal colonic mucosa with a clear interface between the urothelium and colonic mucosa. Conclusions: Successful implantation of colon mucosa into a bladder completely denuded of urothelium was achieved, preserving the anatomy and function of the bladder, upper urinary tract, and kidneys.